The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1747493017706240
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular injury in cryptococcal meningitis

Abstract: Background Cryptococcal meningitis continues to be one of the common causes of chronic central nervous system infection worldwide. Individuals with cryptococcal meningitis can occasionally present with small vessel vasculitis causing infarcts primarily in the basal ganglia, internal capsule, and thalamus. Literature regarding patterns of cerebrovascular injury among patients with cryptococcal meningitis is scanty, and outcome following these vascular involvements is unknown. Aim To study the clinical profile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 20 publications
0
44
3
2
Order By: Relevance
“…24,36,46 Adult studies have found that stroke is not common in HIV without an additional underlying disease state. 47 These disease states include infections including varicella zoster virus, 42 cryptococcus, 48,49 neurocysticercosis, 50 hepatitis B, 51 syphilis, 52 and tuberculosis, 53 as well as neoplastic and prothrombotic states. 47 Immune reconstitution syndrome 54 and ART may also contribute to cerebrovascular disease, with evidence for both protease inhibitors 55 and efavirenz 56 potentially contributing to cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…24,36,46 Adult studies have found that stroke is not common in HIV without an additional underlying disease state. 47 These disease states include infections including varicella zoster virus, 42 cryptococcus, 48,49 neurocysticercosis, 50 hepatitis B, 51 syphilis, 52 and tuberculosis, 53 as well as neoplastic and prothrombotic states. 47 Immune reconstitution syndrome 54 and ART may also contribute to cerebrovascular disease, with evidence for both protease inhibitors 55 and efavirenz 56 potentially contributing to cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Headache is the most common presenting symptom, although fever, vomiting, and altered mental status can also be observed. 2,3 Immunocompetent patients with cryptococcal meningitis are more likely to have subacute, recurrent episodes of nonspecific symptoms like headache, nausea, and CN palsies. 4 Other signs include meningismus, papilledema, focal deficits, and depressed level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular complications are rare [28]; prognosis is determined by the increase in intracranial pressure and the development of papilledema [29][30][31].…”
Section: Cryptococcus Neoformans Sppmentioning
confidence: 99%